Inhibition of α-Glucosidase Activity and The Toxicity of Tristaniopsis merguensis Griff. Leaf Extract - Robby Gus Mahardika; Occa Roanisca; Fajar Indah Puspita Sari (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Abstract : This study aims to determine the antidiabetic activity and toxicity of the acetone extract of Tristaniopsis merguensis Griff leaf. The antidiabetic test was the α-glucosidase inhibition method, while the toxicity test used the Brine Shrimp Lethality Test (BSLT) method. The acetone extract possessed antidiabetic activity with an IC50 value of 8.83 ± 0.31 (μg/mL). This value is not much different from the positive control of quercetin which has an IC50 value of 6.04 ± 0.14 (μg/mL). The characteristics of the FT-IR spectrum of acetone extract showed that Tristaniopsis merguensis leaf has the groups Ar-OH (phenolic), -OH (hydroxyl), C=O (ketone) and C=C (aromatic). Based on the toxicity test, the Tristaniopsis merguensis leaf acetone extract has an LC50 value of 959.25 ppm which means that the acetone extract is toxic. Therefore, the acetone extract of Tristaniopsis merguensis might be the potential agent of antidiabetic.Abstrak : Penelitian ini bertujuan untuk mengetahui aktivitas antidiabetes dan toksisitas dari ekstrak aseton daun Tristaniopsis merguensis Griff. Uji aktivitas antidiabetes ditentukan berdasarkan metode inhibisi enzim α-glucosidase, sedangkan toksisitas ditentukan berdasarkan metode Brine Shrimp Lethality Test (BSLT). Ekstrak aseton memiliki aktivitas antidiabetes dengan nilai IC50 8,83 ± 0,31 (μg/mL). Nilai ini tidak jauh berbeda dengan kontrol positif quersetin yang memiliki nilai IC50 6,04 ± 0,14 (μg/mL). Karakteristik spektrum FT-IR ekstrak aseton menunjukkan bahwa daun Tristaniopsis merguensis memiliki gugus fungsi Ar-OH (fenolik), -OH (hidroksil), C=O (keton) dan C=C (aromatik). Berdasarkan uji toksisitas, ekstrak aseton daun Tristaniopsis merguensis memiliki nilai LC50 sebesar 959,25 ppm yang berarti bahwa ekstrak aseton bersifat toksik. Oleh karena itu, ekstrak aseton dari Tristaniopsis merguensis berpotensi untuk dijadikan agen antidiabetes.